Review of the challenge in Knowledge management to bring innovation in the organizations (Eurasian Journal of Research, Development and Innovation, 2022)
In a world dependent on technology, knowledge management is the most important thing. constantly changing markets and the pursuit of innovation to achieve a competitive advantage. This study aims to explore some of the different variables that influence knowledge management to become an innovation. The study seeks to answer the research question: what is the challenge in knowledge management to bringing innovation to organizations? The goal is to analyze the relationship between KM and innovation and determine whether or not there is an influence and what the challenges are.